2016
DOI: 10.4103/0973-1296.191453
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory and cytotoxic activities of chrysin on human breast adenocarcinoma cells by induction of apoptosis

Abstract: Objectives:Chrysin, an active natural bioflavonoid found in honey and many plant extracts, was first known for its antioxidant and anti-inflammatory effects. The fact that antioxidants have several inhibitory effects against different diseases, such as cancer, led to search for food rich in antioxidants. In this study, we investigated the antiproliferative and apoptotic effects of chrysin on the cultured human breast cancer cells (MCF-7).Materials and Methods:Cells were cultured in Roswell Park Memorial Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 42 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…51 Activated NF-κB induces the pro-inflammatory cytokines, 52 - 54 such as iNOS, 55 COX-2, and microsomal prostaglandin E synthase-1. 56 In addition, inflammation increases cellular reactive oxygen species production by releasing various NF-κB-mediated pro-inflammatory mediators. 57 Therefore, inhibition of microglial activation may be effective for neuronal cell survival.…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…51 Activated NF-κB induces the pro-inflammatory cytokines, 52 - 54 such as iNOS, 55 COX-2, and microsomal prostaglandin E synthase-1. 56 In addition, inflammation increases cellular reactive oxygen species production by releasing various NF-κB-mediated pro-inflammatory mediators. 57 Therefore, inhibition of microglial activation may be effective for neuronal cell survival.…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…Oxidative stress is caused by a disturbance of the balance between oxidative and antioxidative systems, which leads to an impairment of the antioxidative defense [ 23 ]. It has been pointed out that oxidative stress leads to oxidation of lipids, proteins, and DNA, which causes various pathological states [ 23 , 24 , 25 , 26 , 27 , 28 ]. OPs induce oxidative damage by attacking one of the three main MAPK subfamilies, including ERK, JNK, and p38-MAPK kinase.…”
Section: Oxidative Effect Of Organophosphate Pesticides Is Mediatementioning
confidence: 99%
“…One of these natural flavonoids is chrysin, with the chemical structure of 5,7-dihydroxyflavone, which is present in propolis and honey [ 14 ]. The chrysin antitumor activity was documented in various types of human cancer cell lines, including gastric [ 15 ], breast [ 16 ], colorectal [ 17 ], and prostate [ 18 ] cancer cells due to its ability to induce cell apoptosis and cell cycle arrest [ 19 ]. Interestingly, previous studies showed the antitumor potential of chrysin against HCC through p53/Bcl-2/caspase-9 pathway activation [ 20 ] and targeting hexokinase-2 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%